The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms242115598
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immunomodulatory Effects of Codonopsis pilosula Glucofructan on S180 Solid-Tumor-Bearing Mice

Yuting Fan,
Yan Long,
Youshun Gong
et al.

Abstract: The immune functions of the body are intricately intertwined with the onset and advancement of tumors, and immunotherapy mediated by bioactive compounds has exhibited initial effectiveness in overcoming chemotherapy resistance and inhibiting tumor growth. However, the comprehensive interpretation of the roles played by immunologic components in the process of combating tumors remains to be elucidated. In this study, the Codonopsis pilosula glucofructan (CPG) prepared in our previous research was employed as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…[133] C pilosula glucofructan, used as an immunopotentiator in previous research, has been shown to effectively inhibit tumor growth in mice. [134] C pilosula may suppress hepatocellular carcinoma growth by targeting CDK1 and influencing the PDK1/β-catenin signaling pathway, which restricts cell epithelial–mesenchymal transition and diminishes cell stemness, highlighting its potential therapeutic value in liver cancer treatment. [135]…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…[133] C pilosula glucofructan, used as an immunopotentiator in previous research, has been shown to effectively inhibit tumor growth in mice. [134] C pilosula may suppress hepatocellular carcinoma growth by targeting CDK1 and influencing the PDK1/β-catenin signaling pathway, which restricts cell epithelial–mesenchymal transition and diminishes cell stemness, highlighting its potential therapeutic value in liver cancer treatment. [135]…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Therefore, the simultaneous analysis of antioxidant and anti-tumor activities in vitro is commonly conducted by scholars when investigating the biological activity of natural substances [ 19 ]. However, often the impact of direct exposure to free radicals and tumor cells does not accurately reflect the practical applications of bioactive compounds from food raw materials, which indicates the necessity of conducting animal trials in order to ascertain the physiological effects within intricate biological milieu [ 20 ].…”
Section: Introductionmentioning
confidence: 99%